Profile Of Ideal Teachers Of Islamic Education (Study Of Ar Fachruddin Figure) - Zailani Zailani (Proceeding International Seminar of Islamic Studies, 2019)
Profile Teacher Ideal Education Islam is hope for all , used as a guide for teachers Education Islam. At present many teachers are only able to teach , but they have not become role models for their students . Through this research, it will be investigated, how should have been the Ideal Teacher Profile of Islamic Education through the study of AR Fa chruddin's figures. With the goal to be known characters what course which is owned by AR Fachruddin as a teacher worthy of made profiles of teachers Ideal. Type Research This is a study of qualitative , library Reseacrh . By usingprimary and secondary references. Sources that primer is books that was written by AR Fachruddin or who writes about him and there is its relationship with the title of researcher . From discussion found that AR Fachruddin has profile of ideal as teacher Islamic education. He not only taught but as good figure to others. This is worthy of being used as an example for Islamic education teachers .